Prevalence, Prevention, and Lifestyle Intervention of Gestational Diabetes Mellitus in China - Juan, Juan; Yang, Huixia (International journal of environmental research and public health, 2020)
Gestational diabetes mellitus (GDM) has become an epidemic and has caused a tremendous healthy and economic burden in China, especially after the “two-child policy” put into effect on October 2015. The prevalence of GDM has continued to increase during the past few decades and is likely to see a further rise in the future. The public health impact of GDM is becoming more apparent in China and it might lead to the development of chronic non-communicable diseases in the long-term for both mothers and their children. Early identification of high-risk individuals could help to take preventive and intervention measures to reduce the risk of GDM and adverse perinatal outcomes. Therefore, a focus on prevention and intervention of GDM in China is of great importance. Lifestyle interventions, including dietary and physical exercise intervention, are effective and first-line preventive strategies for GDM prevention and intervention. The GDM One-day Care Clinic established in 2011, which educates GDM patients on the basic knowledge of GDM, dietary intervention, physical exercise, weight management, and blood glucose self-monitoring methods, sets a good model for group management of GDM and has been implemented throughout the hospitals as well as maternal and child health centers in China. The current review focus on the prevalence, risk factors, as well as prevention and lifestyle intervention of GDM in China for better understanding of the latest epidemiology of GDM in China and help to improve maternal and neonatal pregnancy outcomes and promote long-term health for women with GDM.